Blue rubber bleb naevus disease: an uncommon cause of gastrointestinal tract bleeding. Issue 10 (October 1988) - Jennings, M; Ward, P; Maddocks, J L
Abstract : A 23 year old woman presented with facial pain, a right parotid tumour and iron deficiency anaemia. She had several cutaneous venous swellings and tumours with a similar appearance were found in the large bowel. Histological examination of the parotid tumour and angiography of the skin and gut lesions confirmed that they were venous in origin. The aetiology, classification, and complications of disorders of the venous system and the importance of using a tourniquet to examine the peripheral veins is discussed.